The role of macrophages in liver fibrosis: composition, heterogeneity, and therapeutic strategies - Ma, Xiaocao; Qiu, Jia; Zou, Shubiao; Tan, Liling; Miao, Tingting (Frontiers in Immunology, 2024)
Macrophages, the predominant immune cells in the liver, are essential for maintaining hepatic homeostasis and responding to liver injury caused by external stressors. The hepatic macrophage population is highly heterogeneous and plastic, mainly comprised of hepatic resident kuffer cells (KCs), monocyte-derived macrophages (MoMφs), lipid-associated macrophages (LAMs), and liver capsular macrophages (LCMs). KCs, a population of resident macrophages, are localized in the liver and can self-renew through in situ proliferation. However, MoMφs in the liver are recruited from the periphery circulation. LAMs are a self-renewing subgroup of liver macrophages near the bile duct. While LCMs are located in the liver capsule and derived from peripheral monocytes. LAMs and LCMs are also involved in liver damage induced by various factors. Hepatic macrophages exhibit distinct phenotypes and functions depending on the specific microenvironment in the liver. KCs are critical for initiating inflammatory responses after sensing tissue damage, while the MoMφs infiltrated in the liver are implicated in both the progression and resolution of chronic hepatic inflammation and fibrosis. The regulatory function of liver macrophages in hepatic fibrosis has attracted significant interest in current research. Numerous literatures have documented that the MoMφs in the liver have a dual impact on the progression and resolution of liver fibrosis. The MoMφs in the liver can be categorized into two subtypes based on their Ly-6C expression level: inflammatory macrophages with high Ly-6C expression (referred to as Ly-6Chi subgroup macrophages) and reparative macrophages with low Ly-6C expression (referred to as Ly-6Clo subgroup macrophages). Ly-6Chi subgroup macrophages are conducive to the occurrence and progression of liver fibrosis, while Ly-6Clo subgroup macrophages are associated with the degradation of extracellular matrix (ECM) and regression of liver fibrosis. Given this, liver macrophages play a pivotal role in the occurrence, progression, and regression of liver fibrosis. Based on these studies, treatment therapies targeting liver macrophages are also being studied gradually. This review aims to summarize researches on the composition and origin of liver macrophages, the macrophage heterogeneity in the progression and regression of liver fibrosis, and anti-fibrosis therapeutic strategies targeting macrophages in the liver.